2023
DOI: 10.1186/s41182-023-00530-y
|View full text |Cite
|
Sign up to set email alerts
|

Unforeseen complications: a case of dengue shock syndrome presenting with multi-organ dysfunction in a subtropical region

Abstract: Overview Dengue fever, a viral illness transmitted by the Aedes mosquito, is capable of causing a range of serious complications, including fulminant hepatic failure, renal dysfunction, encephalitis, encephalopathy, neuromuscular and ophthalmic disorders, seizures, and cardiomyopathy. Case description This report details the case of a 30-year-old lactating woman with no notable medical history who presented to the emergency department with symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Unusual complications of dengue are becoming more common nowadays, however, these complications are not always recognized or understood due to a lack of awareness of these adverse outcomes. Not many studies have been undertaken to document all the complications of dengue expanded syndrome, but so far it is seen to affect the major organs like liver, lung, kidney, heart, and brain 1 . Moreover, neurological manifestations of dengue fever are extremely rare where most reported cases are intracranial hemorrhage, encephalitis, and acute disseminated encephalomyelitis (ADEM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unusual complications of dengue are becoming more common nowadays, however, these complications are not always recognized or understood due to a lack of awareness of these adverse outcomes. Not many studies have been undertaken to document all the complications of dengue expanded syndrome, but so far it is seen to affect the major organs like liver, lung, kidney, heart, and brain 1 . Moreover, neurological manifestations of dengue fever are extremely rare where most reported cases are intracranial hemorrhage, encephalitis, and acute disseminated encephalomyelitis (ADEM).…”
Section: Introductionmentioning
confidence: 99%
“…Not many studies have been undertaken to document all the complications of dengue expanded syndrome, but so far it is seen to affect the major organs like liver, lung, kidney, heart, and brain. 1 Moreover, neurological manifestations of dengue fever are extremely rare where most reported cases are intracranial hemorrhage, encephalitis, and acute disseminated encephalomyelitis (ADEM). In a study conducted between 2014 and 2019 showed only 2.64% of 5821 dengue patients were affected with neurological manifestations.…”
Section: Introductionmentioning
confidence: 99%